Familial Sleep Disorders in Unknown Genetic Syndrome - Lelii, Mara; Baggi, Elena; Senatore, Laura; Bedeschi, Maria Francesca; Dilena, Robertino; Iascone, Maria; Gangi, Silvana; Marchisio, Paola; Patria, Maria Francesca (Journal of Pediatric Genetics, 2020)
Sleep-disordered breathing (SDB) is common in children, especially in those with congenital or genetic diseases. The factors involved include obstructive sleep apnea, disrupted rapid eye movement sleep, and central hypoventilation. Diagnosing and treating SDB in these children have a positive impact on the quality of life of them and their families, reducing the risk of both further impairment of cognitive abilities and cardiopulmonary complications. We report a familial case of SDB with central hypoventilation, in which identification of the disorder in the younger sister led to the unfortunately late diagnosis and treatment of the same condition in the older sister.
Keywords: genetic syndrome; sleep-disordered breathing; hypoventilation